A cross sectional survey of smoking characteristics and quitting behaviour from a sample of homeless adults in Great Britain. (August 2019) - Dawkins, Lynne; Ford, Allison; Bauld, Linda; Balaban, Sema; Tyler, Allan; Cox, Sharon
Abstract: Background: Smoking is a key contributor to health and social inequalities and homeless smoking prevalence rates are 4 times higher than the general population. Research on homelessness and smoking to date has been concentrated predominantly in the US and Australia. This study aimed to describe smoking and quitting behaviour in homeless adult smokers in Great Britain. Data on perceptions of, and willingness to try, e-cigarettes were also gathered. Methods: Cross sectional survey of 283 adult smokers accessing homeless support services in Kent, the Midlands, London and Edinburgh. Participants answered a four-part survey: i) demographics; ii) current smoking behaviour and dependence (including the Fagerström Test of Cigarette Dependence [FTCD]); iii) previous quit attempts; and iv) e-cigarettes perceptions. Results: High levels of cigarette dependence were observed (FTCD: M = 7.78, sd ± 0.98). Although desire to quit was high, most had made fewer than 5 quit attempts and 90% of these lasted less than 24 h. 91.5% reported that others around them also smoked. Previous quit methods used included cold turkey (29.7%), NRT (24.7%), varenicline (22.3%) and bupropion (14.5%). 34% were willing or able to spend £20 or more for an e-cigarette and 82% had tried one in the past although 54% reported that they preferred smoking. Conclusion: We observed high nicotine dependence, few long-term quit attempts, strong desire to quit and amenability to both traditional cessation methods and e-cigarettes. Community embedded and non-routine approaches to cessation may be promising avenues promoting engagement with the homeless community. Likely barriers to uptake include low affordability, preference for cigarettes and high numbers of smoking acquaintances. Highlights: We sampled smokers accessing homeless services across four areas of Great Britain. Homeless smokers were highly nicotine dependent and made few quit attempts. Most quit attempts were cold turkey and rarely exceeded 24 h. Over 80% were willing to use an e-cigarette and had tried one in the past. Barriers to use: low affordability, preference for cigarettes and friends smoking